PERUBAHAN PELAYANAN KLINIK NON-BPJS SEBELUM DAN SETELAH IMPLEMENTASI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN (Studi Kasus di Klinik Utama Rawat Inap Sumber Bahagia, Depok, Jawa Barat) - Gregorius Budi Rooseno Putro; Hari Kusnanto (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: The implementation of the BPJS Kesehatan as a single payer healthcare cover back in 2014 in Indonesia starts a new era of a nationwide coverage of health insurance. Every citizen should be a member of that program, according to the law. The state owned health services are the main providers of the services, along with the private owned hospitals and clinics, as long as they can fulfill the requirements given by the government. But some small clinics are not eligible to met the criteria of the BPJS Kesehatan, resulting in the inability to be the provider. This can lead to the decrease of revenues of those clinics, and can cause bankruptcy. Objective: The main objective of this research is to find few alternative strategies that can be applied by the non-BPJS clinics so they can still gain a significant portion of the health service industry business and even increase their revenues by applying those strategies. Methods: This research is a case study conducted in a clinic called KURI Sumber Bahagia in the city of Depok, West Java, with using both quantitative data of patient visitation, that was analysed using a linear regression technique to determine the signification effect of BPJS Kesehatan, as well as qualitative information gathering by means of interviewing the stakeholders in that clinic. The interview data would help the researcher to explain the phenomena found by the statistics measurements. Results: The statistic results of this research showed a significant decrease (p<0,05) in patient visitation after the implementation of BPJS Kesehatan back in 2014, especially in types of services such as manual labour, sectio caeserea labor, infant immunisation in general, and birth control shots. In contrast, there are several services that showed an increase usage (p<0,05) even after BPJS Kesehatan, such as IUDs services, Hepatitis A shots, and Cervical Cancer shots. Based on the interview conducted afterwards, researcher found on most health services, patients tend choose BPJS than private clinics of the same services because it is cost efficient, but on some services they were willing to pay out of pocket in private clinics because the quality of services or the products that were not available in BPJS Kesehatan (eg. NOVA T brand of IUD). Furthermore, the research also found the increase on services which are not available in BPJS Kesehatan (eg. Hepatitis A shots, Cervical cancer shots). Conclusion: There are significant decreases of patient visitation numbers in KURI Sumber Bahagia clinic since the implementation of BPJS Kesehatan. This phenomenon is responded by the clinic by giving a better quality services and products and also by providing other services in which not covered by BPJS Kesehatan. Differentiation of services and quality services is proven effective to maintain and even increase patient visitation, which in the end can give a good revenues for the clinic.